Functional Near-Infrared Spectroscopy Experiment to Investigate Functional Plasticity in the Auditory Cortex - Tavi, Katya (My University, 2021)
The aim of this thesis was to develop a functional near-infrared spectroscopy (fNIRS) experiment to measure normal hearing adult participants (N = 9) to find whether stimulus-dependent and attention-related activation could be detected in the auditory cortex. The motivation for conducting the present study is to shed light on the effectiveness of using fNIRS to investigate functional plasticity in different patient groups treated for hearing deficits. This would provide a better understanding of functional plasticity in the auditory cortex during hearing impairment and the recovery of hearing. Results revealed a significant intermodal attention effect (stronger activation to sounds during auditory than visual attention), but no significant stimulus-dependent activation (activation to sounds in the absence of auditory attention) nor contralateral attention effects (stronger activation to attended ear sounds in the contralateral hemisphere) in the auditory cortex. This is surprising as based on previous fMRI studies all these effects should be relatively strong and therefore further research is needed to develop experimental designs to reliably detect these effects with fNIRS.
Keywords: functional near-infrared spectroscopy, auditory cortex, functional plasticity, attention-related activation, stimulus-dependent activation, intermodal attention effect, contralateral attention effect